Investigation Of Ecotourism Development Based On Collaboration Between Tinggan Indigenous Peoples And Stakeholders In The Pucak Tinggan Area Of Bali - I Wayan Pantiyasa; I Nyoman Darma Putra; Made Antara; I Wayan Suardana; Ketut Antara (Journal Of Social Science (JoSS), 2024)
This study aims to investigate the response of the Tinggan Indigenous Village community and other stakeholders to the development of collaboration-based ecotourism in the Pucak Tinggan Area. This research adopts an exploratory qualitative approach. Data collection method through distributing questionnaires to the public totaling 120 (purposive sampling) respondents, interviews, documentation, observation, and Focus Group Discussion. The data analysis method used is mixed-methods sequential explanatory analysis to determine community response, and qualitative analysis is used to determine the response of other stakeholders. The results showed that the response of the people of Tinggan Traditional Village strongly agreed with the development of collaboration-based ecotourism in the Pucak Tinggan Area, the Government recognized the importance of collaboration-based ecotourism as an important breakthrough, Entrepreneurs in the region also contributed by creating jobs for the community, academics also support ecotourism planning by considering the need for continuous research and innovation, support from media crews will help in promoting or introducing the Pucak Tinggan area to the wider community, tourists respond positively about the condition of the Pucak Tinggan area which is still natural socio-cultural that is still maintained hospitality. The Desa Adat Tinggan community supports a cooperative economy in the Pucak Tinggan area, benefiting local communities, the government, and the community. They encourage research and innovation, and media support can influence Bali's vision, promoting benefits for society, the environment, and governance.